Factor structure and psychometric properties of the Dispositional Resilience Scale among Brazilian adult patients - Solano, João Paulo Consentino; Bracher, Eduardo Sawaya Botelho; Faisal-Cury, Alexandre; Ashmawi, Hazem Adel; Carmona, Maria José Carvalho; Lotufo, Francisco, Neto; Vieira, Joaquim Edson (Arquivos de Neuro-Psiquiatria, 2016)
Objective Verifying the psychometrics of a Brazilian version of the Dispositional Resilience Scale (DRS-15).Methods Cross-cultural adaptation was done interviewing 65 adult patients. Validation was evaluated by application of the Lipp Brazilian Stress Symptoms Inventory (ISSL), Self-Report Questionnaire (SRQ), and other measures to 575 participants from the psychiatric ambulatories (for borderline personality, anxiety or post-traumatic stress disorders) and non-psychiatric ambulatories (chronic pain, pre-anesthetic consultation and companions for the latter). Temporal stability was verified with 123 participants.Results Exploratory factor analysis yielded a three-factor solution. Psychometrics were acceptable (alpha coefficient, 0.71; intraclass correlation coefficient, 0.81). Correlations with the ISSL, SRQ and other measures were noted except for factor 3. In the psychiatric sample, hardiness scores of borderline patients were lower than those of patients with anxiety disorders.Conclusion This version of the DRS-15 exhibited good reliability in a sample of Brazilian patients; validity was confirmed in two of the scale factors.
Keywords: resilience, psychological; scales; cross-cultural comparisons; validation studies; borderline personality